Analysis of red pepper marketing: Evidence from northwest Ethiopia - Abebe Birara Dessie; Tigabu Dagnew Koye; Abebe Dagnew Koye; Asmamaw Alemu Abitew (Journal of Economic Structures, 2019)
Red pepper is the world's second important vegetable ranking after tomatoes. It is the most common spice type which is produced for both commercial and consumption purposes due to its great role in flavoring, food coloring and source of vitamins and minerals. It is also an important cash crop for households and 68% production is for commercial purpose in Amhara region of Ethiopia. However, empirical evidence is lacking on market chain of red pepper in northwest Ethiopia. Therefore, this research was attempted to analyze the market chain of red pepper and the factors that determine the supply of red pepper to the market. Primary data were collected through a semi-structured interview's schedule administered on 385 red pepper producers and 47 traders selected using simple random sampling technique. Moreover, the survey was supplemented by using secondary data, focus group discussions and key informant interviews. Furthermore, combinations of data analysis methods such as the descriptive and econometrics model were used for data analysis. The producers' survey result revealed that 92.47% of red pepper output was supplied to the market. Moreover, the main receivers of red pepper output were district wholesalers, district retailers and district assemblers (collectors) who possess 60.2%, 13.25% and 10.25%, respectively. This implies that district wholesalers took the lion share across the red pepper market channels. The remaining amount were traded by rural retailer and district urban wholesalers (about 12.12%). Furthermore, the multiple linear regression model result revealed that various policy-relevant variables such as access to extension (p < 0.1), yield (p < 0.01), experience (p < 0.1), off-farm income (p < 0.05) and market price (p < 0.01) influenced the marketable supply of red pepper significantly. Generally, red pepper is one of the most important spice which is mainly produced for commercial purpose yet various production and marketing constraints negatively influenced. Therefore, spice producers, development agents, agricultural experts, research institutions, the Ethiopian government and partner organizations should give special attention for extension service, introducing productive and disease-resistant pepper varieties and infrastructure development to enhance the production and commercial value of red pepper at national and international levels.
Keywords: 330; Red pepper; Market chain; Supply; Trader; Multiple linear regression; Ethiopia